Inside Back Cover: A Combined Approach using Sonochemistry and Photocatalysis: How to Apply Sonophotocatalysis for Biomass Conversion? (ChemCatChem 14/2017). Issue 14 (24th July 2017) - Chatel, Gregory; Valange, Sabine; Behling, Ronan; Colmenares, Juan Carlos
Abstract : The Cover shows the combination of sonochemistry and photochemistry for the catalytic conversion of biomass to produce molecules of interest.In their Concept, G. Chatel et al. discuss the ways in which sonophotocatalysis could open new avenues to valorize biomass into fuels or platform molecules. The authors present their personal recommendations for further investigations in this attractive research field. The last section introduces the challenges that must be met and visionary future perspectives for developing sonophotocatalysis from biomass based substrates. More information can be found in the Concept by G. Chatel et al. onpage 2615 in Issue 14, 2017 (DOI:10.1002/cctc.201700297 ).